2021
DOI: 10.1653/024.103.00413
|View full text |Cite
|
Sign up to set email alerts
|

Light Trap Collections of Mosquitoes (Diptera: Culicidae) Using Dry Ice and Octenol Attractants in Adjacent Mosquito Control Programs

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In this study, height was not a significant driver of C. salinarius abundance. We noted greater trapping success for C. salinarius in northeastern Florida using a combination of light and carbon dioxide at ground level [37]. Culex coronator were significantly more abundant in ground space collections, though only 13 specimens were recovered in total, potentially introducing bias.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, height was not a significant driver of C. salinarius abundance. We noted greater trapping success for C. salinarius in northeastern Florida using a combination of light and carbon dioxide at ground level [37]. Culex coronator were significantly more abundant in ground space collections, though only 13 specimens were recovered in total, potentially introducing bias.…”
Section: Discussionmentioning
confidence: 81%
“…The Anastasia Mosquito Control District (AMCD) of St. Johns County has observed that there is a switch between the salt marsh mosquito species Aedes taeniorhynchus (Weidemann) and Aedes sollicitans (Walker) in several areas based on AMCD's surveillance database, including trap data and human landing counts. The pattern changes detected by traps have been documented in several publications (Henzler et al 2013, Smith et al 2016, Xue et al 2016, Giordano et al 2020. In some years, the reasons for the switch in several areas may be related to the possible impact of land use, land cover/development, weather changes and water quality.…”
mentioning
confidence: 80%
“…Trapping was performed with BG Sentinel traps (Biogents AG, Regensburg, Germany). Because the octenol-based lure has been shown to underestimate mosquito species richness compared to CO 2 -baited traps ( Wilke et al 2019 , Giordano et al 2021 ), we added dry ice as a CO 2 source to attract more mosquitoes. Mosquitoes were sampled bi-weekly, with traps deployed between 08:00 a.m. and 11:00 am and collected 24 h later.…”
Section: Methodsmentioning
confidence: 99%